Outcome of Locking Compression Plate (LCP) by Minimally Invasive Percutaneous Plate Osteosynthesis (MIPPO) in Closed Diaphyseal Fracture of Distal Tibia - Sher Dil Khan, Imtiaz Ahmed Shakir, Muhammad Nadeem Kashmiri, Shahzad Anjum,Obaid Ur Rehman,Nayyar Qayyum, Sher Dil Khan, Imtiaz Ahmed Shakir, Muhammad Nadeem Kashmiri, Shahzad Anjum,Obaid Ur Rehman,Nayyar Qayyum (Journal of Rawalpindi Medical College, 2018)
Background: To determine the outcome of locking compression plate (LCP) by minimally invasive percutaneous plate osteosynthesis (MIPPO) in closed diaphyseal fracture of distal tibia Methods: In this descriptive study patients (n=80)of either gender, 20-45 years of age with diaphyseal fractures of distal tibia were included. While patients having open, pathological, old (>3 wks), infected and fractures associated with compartment syndrome were excluded. All the patients were treated with LCP through MIPPO technique. All patients were discharged 3 days after surgery. The follow up of the patients was done at 2nd, 6th, 8th and 12th week interval. The patients were assessed for the outcome parameters (complications) i.e. delayed radiological union, palpable implant, and ankle stiffness. Results : Mean age of male and female patients was 33.89±7.49 and 31.63±8.55 years respectively. Majority (77.2%) were male. Delayed union was observed in 9.4%. There were 12.2% patients who had palpable hardware. Ankle stiffness was observed in 7.2%. Conclusion: Management of closed distal diaphyseal fractures of tibia with LCP through MIPPO technique is an excellent treatment method as it have increased union rate and decreased complications (Palpable implant and ankle stiffness).